2010
DOI: 10.1631/jzus.b1000020
|View full text |Cite
|
Sign up to set email alerts
|

A microarray analysis of early activated pathways in concanavalin A-induced hepatitis

Abstract: Abstract:Objective: To explore the mechanisms of fulminant hepatitis (FH) in the early stages, and to determine the critical pathways in its initiation and progression. Methods: Twelve BALB/c mice were divided into four groups: one group left as negative control and sacrificed immediately after injection of phosphate-buffered saline (PBS), and another three groups with concanavalin A (Con A) administration sacrificed at 1, 3, and 6 h after injection. Affymetrix GeneChip® Mouse 430 2.0 Array was employed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
(26 reference statements)
3
12
0
Order By: Relevance
“…The extent of liver injury was also evaluated by determining serum ALT, AST, STB, and LDH using the standard Reitman-Frankel method. The results can be seen in our previous articles [16,17] .…”
Section: Cona-induced Hepatitis Model In Micesupporting
confidence: 75%
See 1 more Smart Citation
“…The extent of liver injury was also evaluated by determining serum ALT, AST, STB, and LDH using the standard Reitman-Frankel method. The results can be seen in our previous articles [16,17] .…”
Section: Cona-induced Hepatitis Model In Micesupporting
confidence: 75%
“…Ji-hua XUE, Min ZHENG, Xiao-wei XU, Shan-shan WU, Zhi CHEN, Feng CHEN * npg In a previous study, we obtained the gene expression profile of livers from mice in a concanavalin A (ConA)-induced hepatitis model by GeneChip array [16,17] . ConA-induced hepatic injury in mice has long been established as a model of immunologically induced hepatocyte injury because its histological features highly resemble those of viral or druginduced acute hepatitis in humans [18] .…”
Section: Involvement Of Rest Corepressor 3 In Prognosis Of Human Hepamentioning
confidence: 99%
“…In the liver, TLRs are widely expressed on Kupffer cells, hepatocytes, hepatic stellate cells, biliary epithelial cells, sinusoidal endothelial cells, and hepatic dendritic cells [9][10][11][12][13][14][15], which play critical roles for the liver health [9,10]. Also, the liver is constantly exposed to gut-derived bacterial products, suggesting that bacterial products and TLRs might be involved in liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies indicated that TLRmedicated signals have been involved in almost all liver diseases [7][8][9][10][11][12][13][14][15]. Recent studies implicating TLR2, TLR4 and TLR9 signaling in Con A-induced liver injury are also of particular [10][11][12][13][14][15]. Ojiro K et al [11] found that the TLRs-MyD88 signaling pathway in liver macrophages was critically involved in the pathogenesis of Con A-induced liver damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation